1996
DOI: 10.5636/jgg.48.515
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Two Active Reconnection Sites in the Distant Magnetotail

Abstract: Prior to the observation of fast tailward plasma flows, earthward plasma flows are often observed in the distant magnetotail. By studying the evolution of the ion distribution functions for the transition flow from earthward to tailward flow, we find a multi-layer structure of beamlike plasma flows in the plasma sheet boundary layer, PSBL: 1) earthward, anisotropic beam plasma can be observed in the outer region of PSBL, i.e., the plasma lobe side of the PSBL; and 2) the counterstreaming ions, which consist of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 16 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…This two-point reconnection model has been suggested to interpret a stagnant plasmoid (Nishida et al, 1986;Kawano et al, 1996). Hoshino et al (1996) has also reported evidence for this model with the GEOTAIL observations. An event as shown in Panel A of Fig.…”
Section: Discussionmentioning
confidence: 65%
“…This two-point reconnection model has been suggested to interpret a stagnant plasmoid (Nishida et al, 1986;Kawano et al, 1996). Hoshino et al (1996) has also reported evidence for this model with the GEOTAIL observations. An event as shown in Panel A of Fig.…”
Section: Discussionmentioning
confidence: 65%
“…At the #S2 onset time on 4 September 1999, the auroral intensity in the 557.7 nm emissions at Gillam suddenly appeared at higher latitude and became stronger than those at lower latitudes that gradually declined after the #S1 onset of the second substorm (see Figure 2). By using Geotail observations, Hoshino et al [1996] confirmed the existence of a second distant neutral point in the magnetotail. In addition, Kawano et al [1996] found the sequence of earthward and tailward field‐aligned beam directions when Geotail entered a plasmoid.…”
Section: Discussionmentioning
confidence: 78%
“…We interpret Event 1 as a flux rope, embedded in between the near‐Earth neutral line (NENL) and the distant neutral line. This configuration of two connected reconnection lines is sometimes referred to as an “O‐line” [e.g., Hoshino et al , 1996], since it naturally forms an O‐type neutral line in between the two reconnection sites in a two‐dimensional configuration. The flow reversal at ∼17:19 UT serves as the main argument for the passage of an O‐line.…”
Section: Passage Of An O‐line (Event 1)mentioning
confidence: 99%